2013
DOI: 10.4236/ajac.2013.411073
|View full text |Cite
|
Sign up to set email alerts
|

Application of Artificial Intelligence (AI) Modeling in Kinetics of Methane Hydrate Growth

Abstract: Determining thermodynamic and kinetic conditions for natural gas hydrate formation is an interesting subject for many researches. At the present, suitable information including experimental data and the thermodynamic models of hydrate formation are available which predict the thermodynamic conditions of hydrate formation. Conversely, there is no sufficient study about the kinetics of natural gas hydrate and most of experimental data and kinetic models in the literature are incomplete. Artificial Intelligence (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Based on whether discrete or continuous output features are used, supervised learning can be further divided into classification and regression activities [14]. Several existing ML models, such as Artificial Neural Network (ANN), Gaussian Process Regression (GPR) and other existing ML models, are present in the mitigation of gas hydrate formation [16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Methods and Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Based on whether discrete or continuous output features are used, supervised learning can be further divided into classification and regression activities [14]. Several existing ML models, such as Artificial Neural Network (ANN), Gaussian Process Regression (GPR) and other existing ML models, are present in the mitigation of gas hydrate formation [16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Methods and Theorymentioning
confidence: 99%
“…Besides that, there are 136 water molecules for a unit cell of structure II and enclosed 24 cavities, including 16 smalls and 8 wide ones [14]. It is therefore important to resolve the problem of gas hydrate development by introducing appropriate preventive and predictive strategies [3,16]. There are many risk control techniques that have been used,'such as the use of thermodynamic hydrate inhibitor (THI) inhibitors and low-dose hydrate inhibitor (LDHI) inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…A typical neuron i could be represented by the following equations: r i = j = 1 N ( w i j x j + b i ) y i = f false( r i false) where x j and w ij denote the input signals and the neuron’s synaptic weights, respectively, and r i , b i , y i , and f are the linear combiner output, bias term, output signal of the neuron, and activation function, respectively. The authors of refs and used the back-propagation algorithm to minimize the mean squared error (MSE) of the input and output variables. Also depending on the type of model development, the RBFs might need several hidden layers and a transfer function.…”
Section: Machine Learning Models Used For Gas-hydrate-related Studiesmentioning
confidence: 99%
“…In [14] presented by "Jalal Foroozesh el al", an investigation was formed for the relation-ship between growth rate of methane hydrate with temperature and pressure using Artificial Neural Network and Adaptive Neuro-Fuzzy Inference System (ANFIS). The results have shown that ANIFS is a more potential tool in predication relationship of kinetics of hydrate formation with temperature and pressure in comparison of ANN.…”
Section: A) Hand Calculation Methodsmentioning
confidence: 99%